Leucine-Rich Repeat Kinase 2 Controls the Ca2+/Nuclear Factor of Activated T Cells/IL-2 Pathway during Aspergillus Non-Canonical Autophagy in Dendritic Cells - Wong, Alicia Yoke Wei; Oikonomou, Vasilis; Paolicelli, Giuseppe; De Luca, Antonella; Pariano, Marilena; Fric, Jan; Tay, Hock Soon; Ricciardi-Castagnoli, Paola; Zelante, Teresa (Frontiers in Immunology, 2018)
The Parkinson’s Disease-associated protein, Leucine-rich Repeat Kinase 2 (LRRK2), a known negative regulator of NFAT, is expressed in myeloid cells such as macrophages and dendritic cells (DCs) and is involved in the host immune response against pathogens. Since the Ca2+/NFAT/IL-2 axis has been previously found to regulate DC response to the fungus Aspergillus, we have investigated the role played by the kinase LRRK2 during fungal infection. Mechanistically, we found that in the early stages of the non-canonical autophagic response of DCs to the germinated spores of Aspergillus, LRRK2 undergoes progressive degradation, and regulates NFAT translocation from the cytoplasm to the nucleus. Our results shed new light on the complexity of the Ca2+/NFAT/IL-2 pathway where LRRK2 plays a role in controlling the immune response of DCs to Aspergillus.